MENINGKATKAN KOMPETENSI GURU KELAS MELALUI PELATIHAN PENGGUNAAN MEDIA DAN ALAT PERAGA PEMBELAJARAN IPA DI SDN 04 BEBIDAS KECAMATAN WANASABA TAHUN PELAJARAN 2020/2021 - THURMUDZI THURMUDZI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2021)
This study aims to determine the improvement of Class Teacher Competence in Using Science Teaching Aids through Training on the Use of Teaching Aids at SDN 4 Bebidas, Wanasaba District, Semester 1 (Odd) Academic Year 2020/2021. This workshop and training activity was carried out at SD Negeri 4 Bebidas for the 2020/2021 school year for as many as 9 classroom teachers. In science subjects with competency standards to identify electrical circuits. Data collection and analysis techniques with observation and tests. Based on the results of data analysis, it can be concluded that: the competence of classroom teachers in using science teaching aids at SDN 4 Bebidas, Wanasaba District, Semester 1 (Odd) for the 2020/2021 Academic Year is more improved and better. ABSTRAKPenelitian ini bertujuan untuk mengetahui peningkatan Kompetensi Guru Kelas Dalam Menggunakan Alat Peraga IPA Melalui Pelatihan Penggunaan Alat Peraga di SDN 4 Bebidas Kecamatan Wanasaba Semester 1 (Ganjil) Tahun Pelajaran 2020/2021. Kegiatan workshop dan pelatihan ini dilaksanakan di SD Negeri 4 Bebidas tahun pelajaran 2020 / 2021 pada sebanyak 9 gurukelas. Pada mata pelajaran IPA dengan standar kompetensi mengidentifikasi rangkaian listrik. Teknik pengambilan dan analisis data dengan observasi dan tes. Berdasarkan hasil analisis data dapat disimpulkan bahwa: kompetensi guru kelas dalam menggunakan alat peraga IPA di SDN 4 Bebidas Kecamatan Wanasaba Semester 1 (Ganjil) Tahun Pelajaran 2020/2021 lebih meningkat dan baik.